2017
DOI: 10.1186/s12906-016-1545-7
|View full text |Cite
|
Sign up to set email alerts
|

ViscumTT induces apoptosis and alters IAP expression in osteosarcoma in vitro and has synergistic action when combined with different chemotherapeutic drugs

Abstract: BackgroundOsteosarcoma is the most common bone tumor and is associated with a poor prognosis. Conventional therapies, surgery and chemotherapy, are still the standard but soon reach their limits. New therapeutic approaches are therefore needed. Conventional aqueous mistletoe extracts from the European mistletoe (Viscum album L.) are used in complementary cancer treatment. These commercial extracts are water-based and do not include water-insoluble compounds such as triterpenic acids. However, both hydrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
4
19
0
1
Order By: Relevance
“…TUNEL assay labelling the 3 OH ends of apoptotic nucleus showed an intense brown staining of nucleus of 4T1 cells treated with DSS extract, which means that the extract triggers cell death by apoptosis. This result was confirmed by caspase-3 activation and PARP-1cleavage [49]. Caspase-3 activation and PARP-1 deactivation were found in cells treated with DSS extract in 12 h treatment with DSS but not with DSC.…”
Section: Discussionsupporting
confidence: 54%
“…TUNEL assay labelling the 3 OH ends of apoptotic nucleus showed an intense brown staining of nucleus of 4T1 cells treated with DSS extract, which means that the extract triggers cell death by apoptosis. This result was confirmed by caspase-3 activation and PARP-1cleavage [49]. Caspase-3 activation and PARP-1 deactivation were found in cells treated with DSS extract in 12 h treatment with DSS but not with DSC.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, the impact of caspase-8 has to be investigated in other neuroblastoma cell lines in further studies. However, activation of both intrinsic and extrinsic apoptosis pathways due to mistletoe treatment was reported by other authors [32,33]. The fact that mistletoe extracts can act via activation of both caspase-8 and caspase-9 makes them suitable for the treatment of neuroblastoma, as caspase-8 inactivation (e.g., by DNA hypermethylation) is a frequent virtue of apoptosis resistance in neuroblastoma [30,34].…”
Section: Discussionmentioning
confidence: 92%
“…This result is in line with the assumption that whole plant extracts can be more effective than their single constituents [ 52 54 ]. Synergistic effects of viscumTT were already recently shown in other paediatric tumour cell lines [ 41 44 ].…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies showed the efficacy of a combined mistletoe extract produced by addition of solubilised triterpene acids ( TT ) to aqueous mistletoe extracts ( viscum ), creating a whole plant extract ( viscumTT ). This whole plant extract effectively induced apoptosis in acute myeloid and lymphoblastic leukaemia [ 41 , 42 ], Ewing-sarcoma [ 43 ], and osteosarcoma [ 44 ] and inhibited tumour growth in murine melanoma in vivo [ 45 ]. The aim of this study was to analyse the effect of the whole mistletoe extract, viscumTT , on rhabdomyosarcoma in vitro, ex vivo, and in vivo.…”
Section: Introductionmentioning
confidence: 99%